ACHIEVING STABLE EXCHANGE: USING SOCIAL PENETRATION THEORY TO EXPLORE THE MARRIAGE COUNSELLING PROCESS OF MAWAR SARON CHURCH SURABAYA - Santoso, Theodore; Haryono, Cosmas Gatot (ASPIKOM Jabodetabek Region, 2023)
A This study aims to investigate strategies used in Indonesian marriage counselling. How they engage in social penetration, encourages adversarial parties to be more forthcoming and produce stable exchanges. By gathering counseling cases at the Mawar Saron Church in Surabaya, the research was carried out utilizing qualitative research techniques. The theory that is applied is social penetration theory, which views self-disclosure as developing gradually. The findings of this study demonstrate that marriage therapy counselors place a high value on neutrality, dependability, and attentive listening. These three elements are used to ensure that counseling sessions go well and result in the best possible resolution for troubled couples.